1999
DOI: 10.1183/09031936.99.13354699
|View full text |Cite
|
Sign up to set email alerts
|

The presence and sequence of endotracheal tube colonization in patients undergoing mechanical ventilation

Abstract: Endotracheal tube colonization in patients undergoing mechanical ventilation was investigated.In the first part of this prospective study, the airway access tube was examined for the presence of secretions, airway obstruction and bacterial colonization, in cases undergoing extubation or tube change. In the second part of the study, the sequence of oropharyngeal, gastric, respiratory tract and endotracheal tube colonization was investigated by sequential swabbing at each site twice daily for 5 days in consecuti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
141
1
8

Year Published

2000
2000
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 217 publications
(153 citation statements)
references
References 22 publications
3
141
1
8
Order By: Relevance
“…The pathogenesis of VAP and NVHAP may differ in several ways. Feldman et al documented the rapid development colonization in the oropharynx, stomach, lower airways and endotracheal tube in patients under mechanical ventilation [20]. The dynamics of colonization is dependent on the extensive and aggressive manipulations to which those patients are exposed.…”
Section: Discussionmentioning
confidence: 99%
“…The pathogenesis of VAP and NVHAP may differ in several ways. Feldman et al documented the rapid development colonization in the oropharynx, stomach, lower airways and endotracheal tube in patients under mechanical ventilation [20]. The dynamics of colonization is dependent on the extensive and aggressive manipulations to which those patients are exposed.…”
Section: Discussionmentioning
confidence: 99%
“…One study demonstrated that 84% of endotracheal tubes examined had a biofilm (188). As documented by Inglis et al, this biofilm is heavily laden with bacteria, usually gram-negative organisms (66,89). At present, ongoing studies are directed at either eliminating this biofilm or reducing the bacterial load associated with it.…”
Section: Preventionmentioning
confidence: 99%
“…Previous studies have reported a high concordance of bacterial culture results between tracheal aspirate samples and ET biofilms (8,23). For example, in a previous study conducted among adults undergoing mechanical ventilation in Spain, identical microorganisms with ET biofilms were isolated in 56% of tracheal aspirate samples (8).…”
Section: Discussionmentioning
confidence: 98%
“…in ET biofilms. Feldman et al (23) reported the time sequence of bacterial colonization in VAP patients, and demonstrated that potential pathogens first colonized the oropharynx and then the lower respiratory tract. Therefore, there may be a high consistency of bacteria between oropharynx and ET biofilms in the early stages of VAP.…”
Section: Discussionmentioning
confidence: 99%